Influence of electrolyte co-additives on the performance of dye-sensitized solar cells - Stergiopoulos, Thomas (Springer, 2011)
The presence of specific chemical additives in the redox electrolyte results in an efficient increase of the photovoltaic performance of dye-sensitized solar cells (DSCs). The most effective additives are 4-tert-butylpyridine (TBP), N-methylbenzimidazole (NMBI) and guanidinium thiocyanate (GuNCS) that are adsorbed onto the photoelectrode/electrolyte interface, thus shifting the semiconductor's conduction band edge and preventing recombination with triiodides. In a comparative work, we investigated in detail the action of TBP and NMBI additives in ionic liquid-based redox electrolytes with varying iodine concentrations, in order to extract the optimum additive/I2 ratio for each system. Different optimum additive/I2 ratios were determined for TBP and NMBI, despite the fact that both generally work in a similar way. Further addition of GuNCS in the optimized electrolytic media causes significant synergistic effects, the action of GuNCS being strongly influenced by the nature of the corresponding co-additive. Under the best operation conditions, power conversion efficiencies as high as 8% were obtained.